Research on the Core Competence Training System for Health Service and Management Majors in Universities under the New Medical Science Context - Xing, Jianhong (Education Insights, 2026)
The construction of the new medical science paradigm emphasizes the comprehensive cross-integration of traditional medicine with engineering, management, humanities, and social sciences. This interdisciplinary approach serves as an essential mechanism to adapt to the Healthy China strategy and to cultivate highly versatile professionals for the rapidly expanding big health industry. As an emerging and highly interdisciplinary field, the health service and management major currently encounters several critical challenges in higher education. These include an unclear positioning of core competencies, insufficient integration between medical and management disciplines, a highly fragmented curriculum system, lagging digital skills training, and relatively weak industry-academia collaboration. Based on the fundamental educational orientation of the new medical science context, this paper systematically defines five essential core competencies required for modern professionals: basic medical services, intelligent processing of health data, health management and operation, health promotion practice, and comprehensive professional qualities. To address existing educational gaps, this study constructs a comprehensive, closed-loop training system encompassing "goals, courses, practice, teachers, and evaluation." Furthermore, it establishes a systematic technical route alongside a multi-dimensional guarantee mechanism, proposing targeted optimization paths for educational reform. Ultimately, this research provides a robust theoretical foundation and valuable practical references for universities seeking to restructure their training models for health service and management talents. By implementing these strategies, academic institutions can significantly enhance students' overall job competence and better adapt to the dynamic development of the global digital health industry.